2012
DOI: 10.1159/000346139
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Concentrations of Anti-Müllerian Hormone Are Common in 53 Female Childhood Cancer Survivors

Abstract: Background/Aims: Gonadal dysfunction is one of the major endocrinological late effects among childhood cancer survivors (CCSs). Periodic screening evaluation of gonadotropins and sex steroids has been recommended, although it remains difficult to predict gonadal function and reproductive capacity in childhood. We evaluated the effects of cancer treatments on the ovarian function of Japanese female CCSs by measuring serum levels of anti-Müllerian hormone (AMH) and gonadotropin. Methods: This was a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Total body irradiation and/or high doses of alkylating agents, such as cyclophosphamide or busulphane, led to ovary dysfunction. Similar results have been reported by Miyoshi et al, who found low AMH levels in 53% and high FSH in 30% of childhood cancer survivors [14]. Fong et al observed accelerated loss of primordial follicles in females after TBI before stem cell transplantation [15].…”
Section: Discussionsupporting
confidence: 82%
“…Total body irradiation and/or high doses of alkylating agents, such as cyclophosphamide or busulphane, led to ovary dysfunction. Similar results have been reported by Miyoshi et al, who found low AMH levels in 53% and high FSH in 30% of childhood cancer survivors [14]. Fong et al observed accelerated loss of primordial follicles in females after TBI before stem cell transplantation [15].…”
Section: Discussionsupporting
confidence: 82%
“…3 In prepubertal females, an AMH plasma level can differentiate between female virilization caused by the presence of testicular tissue or a granulosa cell tumour, and virilization caused by increased adrenal androgen expression. 10,12,13 Furthermore, AMH has also shown potential as a marker for polycystic ovarian syndrome (PCOS) in adolescents, showing a raised concentration compared to controls 14,15 which correlates with ovarian volume 16 and androgen level. 9 Although low at birth in females, AMH increases slightly through childhood and decreases to undetectable levels shortly before clinical menopause.…”
Section: Introductionmentioning
confidence: 99%
“…11 AMH can provide a particularly useful marker of ovarian reserve in the prepubertal population, where FSH is not a reliable measurement; and where assessment may be required for patients who may be about to undergo cranial irradiation or treatment with gonadotoxic agents as part of cancer therapy enabling decisions around egg harvesting. 10,12,13 Furthermore, AMH has also shown potential as a marker for polycystic ovarian syndrome (PCOS) in adolescents, showing a raised concentration compared to controls 14,15 which correlates with ovarian volume 16 and androgen level. 17 Commercial assays for the measurement of circulating anti-Müllerian hormone (AMH) have been available for many years.…”
Section: Introductionmentioning
confidence: 99%
“…24 Some studies have evaluated AMH levels in patients with cancer and chemotherapy. 17,25,26 Retrospective studies have evaluated the prevalence of ovarian failure in SLE patients treated with cyclophosphamide, determining ovarian failure based on the presence or absence of amenorrhea, which is very sensitive and specific. More recently AMH has been used for measurement in SLE patients with and without immunosuppressants and a relationship has been found with the use of cyclophosphamide, but not with the use of other immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%